Orthodontic Treatment in Pediatric Patients with Autism Spectrum Disorder: Compliance and Satisfaction: Pilot Study - Gianni Di Giorgio; Denise Corridore; Ida Carmen Corvino; Giulia Zumbo; Nicola Pranno; Iole Vozza; Antonella Polimeni; Maurizio Bossù (Applied Sciences, 2023)
Background: Most children with ASD require orthodontic treatment to correct a malocclusion, to restore masticatory function, and for cosmetic reasons. The use of orthodontic devices, however, could lead to a distortion of the child’s routine, causing mood alterations, on the one hand, and a worsening of their oral hygiene status, on the other. The aim of this study is to evaluate the impact of orthodontic therapy on the daily management and level of collaboration of children with ASD determined using the Frankl scale. Materials and methods: An anonymous questionnaire was administered to 20 pairs of parents of children in which they were asked to evaluate any behavioral changes and/or difficulties encountered at the beginning of orthodontic treatment as well as their degree of satisfaction with the level of information received from medical personnel. Results: In about half of the sample, there were behavioral changes and difficulties in managing the treatment. Most of the responses received indicated parental satisfaction both with regard to the emotional impact on the children with respect to the introduction of the treatment and with regard to the attention received from the medical staff. Furthermore, there was a statistically significant increase (p = 0.001) in the Frankl scale score after treatment. Conclusions: Home management, which has always been the most difficult obstacle to overcome, with the support of a competent team can not only improve the quality of life of patients affected by ASD but also improve their collaboration and state of oral health without altering their emotionality.